2014
DOI: 10.3389/fnhum.2014.00221
|View full text |Cite
|
Sign up to set email alerts
|

Pupillary behavior in relation to wavelength and age

Abstract: Pupil light reflex can be used as a non-invasive ocular predictor of cephalic autonomic nervous system integrity. Spectral sensitivity of the pupil's response to light has, for some time, been an interesting issue. It has generally, however, only been investigated with the use of white light and studies with monochromatic wavelengths are scarce. This study investigates the effects of wavelength and age within three parameters of the pupil light reflex (amplitude of response, latency, and velocity of constricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 47 publications
(57 reference statements)
3
30
0
1
Order By: Relevance
“…However, past psychophysical studies have largely predated the discovery of the melanopsin system and thus did not account for its properties in their methodological design. 21,[27][28][29][36][37][38][39][40] For example, retinal response features differ with stimulus wavelength, 41 and given the photoncounting feature of the ipRGC system (namely a sustained pupillary constriction that persists after stimulus offset 6 ), a preexposure bias likely exists, particularly in studies that evaluate chromatic responses separately. 21,42 In addition, variable pupil diameter across trials may have altered the proportion of photons that reach the retina, thus two different light intensities may have elicited a similar perceptual experience and biased the discomfort thresholds generated.…”
mentioning
confidence: 99%
“…However, past psychophysical studies have largely predated the discovery of the melanopsin system and thus did not account for its properties in their methodological design. 21,[27][28][29][36][37][38][39][40] For example, retinal response features differ with stimulus wavelength, 41 and given the photoncounting feature of the ipRGC system (namely a sustained pupillary constriction that persists after stimulus offset 6 ), a preexposure bias likely exists, particularly in studies that evaluate chromatic responses separately. 21,42 In addition, variable pupil diameter across trials may have altered the proportion of photons that reach the retina, thus two different light intensities may have elicited a similar perceptual experience and biased the discomfort thresholds generated.…”
mentioning
confidence: 99%
“…More importantly however, because light stimuli used in PLR studies differ in intensity and duration (e.g. 200 ms for PLR versus 4 ms for ERG and VEP) from light stimuli used in ERG and VEP studies, it is difficult to interpret the Lobato- Rincon et al (2014) findings in the context of ours. In contrast, a brief review of existing literature-where photic stimuli were delivered as full-field (Ganzfeld) rather than a point light source-does not support the scenario that pupil constriction affected our ERG and VEP results.…”
Section: Sirmentioning
confidence: 72%
“…If this were the case in our study, one would expect to find smallest pupillary constriction response to blue light, largest to green light and somewhere in between to red and amber lights. In support of this scenario, Dr Mahroo cites a study by Lobato-Rincon et al (2014), which shows that the amplitude and latency of pupil constriction in response to green light is larger than blue and red lights.…”
Section: Sirmentioning
confidence: 95%
“…As already mentioned, age is a major factor in many parameters of the PLR and should be accounted for in all studies [14]. Older participants show decreased amplitude of response [21], increased latency and in some cases decreased velocity [20] as well.…”
Section: Factors Influencing Pupil Reactivitymentioning
confidence: 94%
“…One such study used [20] isoluminant (5 lux at the cornea) white, blue (450 nm), green (510 nm) and red (600 nm) light. They reported that the white and green light conditions had the greatest amplitude and shortest latency times.…”
Section: The Pupillary Light Responsementioning
confidence: 99%